Дораз бертэ тылобурдо но: кылбуръёс / Анатолий Волков - Волков Анатолий Григорьевич (Удмуртия, 1991)
Экземпляры: ф.3 (1991) / Инвентарный номер: 34064 / Цена: / Сис.шифр: 84(2Рос=Удм)6-5 / Авт.знак: В 67 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6-5